TEMPORAL VARIATION IN LARVAL ABUNDANCE OF THE MANGROVE OYSTER Crassostrea sp. IN AN ESTUARY OF SOUTHERN BRAZIL - Castilho-Westphal, Gisela Geraldine; Ostrensky, Antonio (Archives of Veterinary Science, 2017)
An alternative for reducing the degree of exploitation of natural oyster banks is to use artificial seed collectors. The effectiveness of said seed collectors, however, depends on the knowledge of the cycles and abundance of larvae in the plankton. This work aimed to study the presence of larvae of the genus Crassostrea in the Guaratuba Bay, which is located on the southern coast of Brazil, using two complementary methods: 1) visual identification followed by larval counts and 2) identification of the larvae at the species level using molecular biology. Measurements of abiotic parameters related to water quality (concentration and saturation of dissolved oxygen, pH, temperature, salinity and transparency) were performed every two weeks at three sampling points (Cabaraquara, Ilha da Sepultura and Parati) from January 2010 to April 2011 (n=32), and plankton was collected in 65 µm nets for larval research. Environmental parameters, particularly pH and the concentration of dissolved oxygen, influenced the presence of mollusc larvae in the Guaratuba Bay. The highest concentrations of larvae in the plankton occurred between September 2010 and January 2011, and the variation in larval abundance was observed mainly during the warmer seasons of the year (spring and summer).